Sound environment of Cities - Susan Abd Hassan (Iraqi Journal of Architecture and Planning, 2018)
The sound environment in the Traditional Baghdad city specified with soundelements and relationships between sounds that define human sound environment, andhad the greatest impact where natural sounds as human voice, animal and natural soundin addition to the voices of the traditional industries and the old means of transportation.The Recent changes in the traditional urban fabric that accompanied with therequirements of contemporary life. Of transportation, machinery and various industriesaffected in the structure of the traditional Baghdad urban fabric and Incision straightroads to the movement of vehicles and concentration height buildings on both sides ofthese roads, with the changing pattern of use of residential to commercial, affected onthe sound environmental and on perceptional preference for the traditional city .For thisreason, An analytical methods and questionnaire studies were conducted in several areasin Al-Kadhimiya city as an example of the traditional cities. The areas included a widerange of sound types and different sound level, from highly traffic-noise in AkkadStreet to quiet Al-zuqaq (traditional street).Consistent relationships were found betweenmeasured overall sound levels and perceived sound quality, however, sound sourceidentification was found to be a stronger predictor of sound quality than measuredsound levels. Sound quality was negatively related to presence of technological sounds(e.g., road-traffic noise, gasoline generators) in modern type of City Street andpositively related to presence of nature sounds in traditional street.